Charity hazard in climate adaptation: The effect of anticipatory cash transfers on demand for weather insurance - Julian Roeckert; Lukas Mogge; Svenja Fluhrer; Kati Krähnert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2026)
This study examines whether receiving anticipatory cash transfers during an extreme winter affects households' demand for index-based livestock insurance. We exploit a randomized field experiment conducted during the 2020/21 winter disaster in western Mongolia and combine household panel survey data with administrative insurance records. We do not find evidence of charity hazard: the estimated effect of anticipatory cash transfers on insurance uptake is small and statistically indistinguishable from zero. The 95% confidence interval rules out large crowding-out effects but remains consistent with small negative effects of up to 2 percentage points. Treatment effects are heterogeneous: among households with prior insurance experience, estimated effects are positive and statistically significant, while effects among previously uninsured households are statistically indistinguishable from zero. These findings suggest that, in contexts where assistance is incomplete and index insurance is well-established, anticipatory assistance does not need to undermine insurance demand. – – Diese Studie untersucht, ob der Erhalt antizipativer Geldtransfers während eines extremen Winters die Nachfrage von Haushalten nach indexbasierter Viehversicherung beeinflusst. Hierfür nutzen wir ein randomisiertes Feldexperiment, das während der Winterkatastrophe 2020/21 in der Westmongolei durchgeführt wurde, und kombinieren Paneldaten aus Haushaltsbefragungen mit administrativen Versicherungsdaten. Wir finden keine Hinweise auf "Charity Hazard": Der geschätzte Effekt antizipativer Geldtransfers auf den Abschluss von Versicherungen ist gering und statistisch nicht von null zu unterscheiden. Das 95%-Konfidenzintervall schließt große Verdrängungseffekte aus, bleibt jedoch mit kleinen negativen Effekten von bis zu 2 Prozentpunkten vereinbar. Die Effekte der Geldtransfers sind heterogen: Unter Haushalten mit vorheriger Versicherungserfahrung sind die geschätzten Effekte positiv und statistisch signifikant, während die Effekte bei zuvor nicht versicherten Haushalten statistisch nicht von null zu unterscheiden sind. Diese Ergebnisse deuten darauf hin, dass in Kontexten, in denen Unterstützung unvollständig ist und indexbasierte Versicherungen bereits etabliert sind, antizipative Hilfe die Nachfrage nach Versicherungen nicht reduzieren muss.
Keywords: G22; H84; Q12; Q54; 330; Anticipatory humanitarian assistance; extreme weather events; impact evaluation; index-based insurance; randomized controlled trial; Mongolia